Chimerism: A New Look - Nikbin, Behrouz; Talebian, Fatemeh; Mohyeddin, Mandana (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: Microchimerism has become a familiar term in the past few years. Many groups all over the globe, specializing in a diverse array of basic and medical sciences, have turned their attention to microchimerism, its possible role in disease or repair, and its mechanism of action in the host body. We reviewed the current knowledge about this novel term. Materials and Methods: We search the PubMed, using all the derivatives of chimera. All papers and their bibliographic information published by December 2005 were reviewed and 61 were selected. Results: Microchimerism is the presence of foreign or nonhost cells in a body. These are cells that live, differentiate, and persist in the host body by definition. These cells can enter the host body in a variety of manners. The most familiar aspect is microchimerism resulting from organ transplant. For many years now scientists have been debating over the interpretation of this phenomenon. We know that donor cell engraftment in the recipient body is a sign of transplantation success. What this means is that the body has developed tolerance toward the foreign organ and created a chimer. Conclusion: How long this chimeric state will last, whether these cells will induce or be induced to create a chronic complication in the long run, or will these genetically distinct cell types live peacefully in one body to the end of the hostâ€™sÂ  life are the essence of the ongoing discussion and what probes researchers to continue their search.